Penerapan Algoritma Semut pada Protokol Routing AOMDV untuk Optimasi Pencarian Rute di Jaringan VANET - Ni Desak Ketut Pujika Dewi; Andy Hidayat Jatmika; Ariyan Zubaidi (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2020)
VANET is a wireless network that is a derivative of the MANET network. VANET network is one network that can be used to communicate between one vehicle and another vehicle. With the existence of the VANET network, it is expected to be able to improve the safety of drivers on the highway. One of the uses of the AOMDV routing protocol is that it can be used to help the performance of the VANET network, the AOMDV routing protocol. AOMDV routing protocol in conducting route search there are two working mechanisms namely route discovery and route maintenance. The route selection process in the AOMDV routing protocol is to consider the number of hops contained in the AOMDV routing protocol, so that the possibility of a broken link, therefore the need for the application of the method in conducting this research. The ant algorithm is one method that can optimize the process of finding a route in the AOMDV routing protocol. The ant algorithm in carrying out the route search is by calculating the distance between nodes. In the ant algorithm, the route selection is based on the most powerful pheromones, so the route chosen is no longer based on the number of hops. From the results of trials that have been carried out on the AOMDV routing protocol using the ant algorithm can improve the performance of the test throughput parameters of 9.7649 Kbps and the performance of the Packet Delivery Ratio of 11.2838%. Whereas the average end to end delay parameter can reduce the delay by 13.3093ms